A house built on sand– waterfront views and primordial seas: Job 38, Matthew 7, coastal erosion, and beachfront development. (February 2017) - Miller, Liam
This article begins with an examination of the state of coastal erosion at Collaroy and Narrabeen Beaches in NSW, Australia. In light of recent severe storms, which damaged the homes along the beachfront, and the increasing awareness of the coastal erosion caused by such properties there is a need to determine what lies beneath the decision to continue to develop along Australian beachfronts. Taking an ecotheological approach this article proposes that the philosophical and theological concepts of hubris and foolishness characterize these decisions, and the desire to live so close to the coast. In response to this, ecotheological readings of Job 38 and Matthew 7 are proposed to help provide an ecologically conscious and environmentally stable way forward. In Job 38 God speaks out of the whirlwind declaring that it was God who 'shut the sea in with doors' telling the waves 'thus far shall you go and no farther'. By persisting with beachside development in light of our growing ecological awareness humans breach and encroach upon the natural and, perhaps, God-ordained borders between the sea and the land. In Matthew 7 Jesus compares the foolish, who refuse to act when they hear, to someone who 'built his house on sand'. By refusing to heed and act in light of the growing ecological crisis and coastal erosion, and examples such as the 300 million Collaroy/Narrabeen coastline, beachfront developers are perhaps examples of Jesus' fool. How might the church contribute to conversations within, and critiques of, a culture which places such a high esteem on proximity to the ocean that it would risk both human homes and non-human ecology?